Next Generation Sequencing (NGS) approach applied to species identification in mixed processed seafood products. (March 2022) - Piredda, Roberta; Mottola, Anna; Cipriano, Giulia; Carlucci, Roberto; Ciccarese, Giuseppina; Di Pinto, Angela
Abstract: Multi-species fish products are a growing market segment driven by several inputs, including urbanization, modern lifestyles and the availability of new technologies. These products are characterized by the absence of species-related morphological traits, as well as by the use of discards or fish waste as ingredients, that cannot be traced using a classical molecular approach. This historic inability to identify ingredients, coupled with a rather lean list of mandatory information required by current legislation, make these products the perfect target for substitution fraud. New molecular tools are now available to overcome this gap, such as the metabarcoding approach which can be used to trace species from complex food matrices. In this study, we used such an approach to sequence a fragment of 16S rRNA mitochondrial gene from 20 multispecies processed seafood products, sold on the Italian market and including breaded, burger and surimi, in order to evaluate mislabelling rates and formulate hypotheses regarding the potential drivers of fraudulent activities. Our results highlighted the presence of 120 marine taxa with an overall mislabelling rate of 45%, including some low-abundance taxa not included in the current Italian legislation, found mainly in the surimi samples. The presence of Tetraodontidae and swine DNA raise concerns regarding consumer safety and protection with regard to ethical or religious issues, as well the inclusion of undeclared molluscs potentially causing allergies. The high number of low-frequency taxa confirms the inclusion of discards and fish waste, doubtless positive for sustainable fisheries, but also boosting profits for the fish industry. Such practice, however, without an adequate labelling and traceability system, is a source of risk for consumers and marine ecosystems. In this context, a revision of national and international food safety legislation is needed; indeed, metabarcoding assessments can provide useful information to stakeholders and act as the future operational tool for inspective monitoring. Highlights: NGS metabarcoding is powerful tool for multi-species fish products authentication. High number of taxa are contained as ingredients in multi-species fish products. Tetraodontidae and swine presence poses implications for the consumer protection. In absence of control, the use of discards and fish waste can include risks. A revision of food safety legislation for these products is needed.